Metallurgy technology and materials. VII : selected, peer reviewed papers from the 7th International Conference on Metallurgy Technology and Materials (ICMTM 2019), June 14-15, 2019, Xiamen, China - Nor Sabirin, Mohamed (Trans Tech Publications, Ltd., 2019)
This volume contains papers which were presented at the 7th International Conference on Metallurgy Technology and Materials (ICMTM2019, June 14-15, 2019, Xiamen, China) and presents to readers the recent research results in the area of materials science and materials processing technologies. Steel, Alloys, Corrosion, Mechanical Properties, Microstructure, Wear Resistance, Processing Technologies, Biotechnology, Absorption, Extracting, Chemical Technology, Polymers, Composites, Cement, Ceramics, Semiconductors, Thin Films, Graphene, Nanotubes, Functional Materials Materials Science, Building Materials, Mechanical Engineering.
Keywords: Metals -- Finishing -- Congresses.; Protective coatings -- Congresses.; elektronické knihy; electronic books